A Methods engineering study on the Southern Glory International Printing Department - Ayes, Sheryl; Olfindo, Vanessa; Pereyra, Janice (Diliman, Quezon City College of Engineering, 2000)
As a Methods Engineering Study, the research group conducted the investigation and documentation of the existing procedures in the printing department of the company of the name Southern Glory International. This study is guided by the knowledge obtained from the class lectures of the course Industrial Engineering 32, and is directed through several goals. The primal of which is the identification of deviating conditions in the systems and procedures of the company, the verification of those, and the seeking of the feasible alternative solutions. In the course of the study, the group has identified several departures from the ideal by employing the tools like Brainstorming, Streamline Analysis and Ishikawa Analysis. Those are : insufficient control; the lack of standard performance times, lack of interest of workers in their jobs; nonchalance of the workers in the job; poor worker motivation; operations manually done, inviting bodily strains; poor production planning; poor workplace layout. For these problems, the group has generated two alternatives. These alternatives only focus on the workplace layout. This is since the operations of the printing department is labor intensive such that any change that could improve the entire printing process would already involve the employment of machines, thereby making the alternatives formidable to implement. In these alternatives, the first focused on the degree of importance and unimportance of the closeness between the different sections of the printing department. Thus, those sections that are desirable to be close to one another are placed near each other for easier movement of both workers and materials. The second alternative, on the other hand, focused on space utilization. It aims to utilize the space in the printing department's warehouse, which the group believed to be idle. In this alternative, the mixing, pressing and inspection section were moved to the referred to area. Thus, more space was allocated for printing and for both movements of materials and workers. Furthermore, this alternative provides better air circulation, thus improving the working condition. In the evaluation of the alternatives, both proved to be almost balanced, meaning that they have no huge difference from each other. The group therefore recommends that both alternatives be considered. Although this study guaranteed the group's fulfillment, there are still some areas that could be studied further.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis